Video head impulse test relevance in the early postoperative period after cochlear implantation. (2nd January 2019) - Bittar, Roseli Saraiva Moreira; Sato, Eduardo; Ribeiro, Douglas Josimo Silva; Oiticica, Jeanne; Grasel, Signe Schuster; Mezzalira, Raquel; Tsuji, Robinson Koji; Bento, Ricardo Ferreira
Abstract: Background: Cochlear implantation (CI) is the gold standard therapy for profound or severe sensorineural hearing loss. It is a safe surgical procedure but, because of the proximity of the cochlea and vestibule, postoperative vestibular disorder may occur. Our hypothesis is that the video head impulse test (vHIT) may be a good tool to achieve a topographic diagnosis of dizziness in the early postoperative period after CI. Aims/Objectives: To evaluate patients with instability, imbalance and vertigo between 7 and 14 days after CI procedure. Material and methods: A total of 31patients scheduled for unilateral CI were included in this study. vHIT for horizontal semicircular canal was performed before CI and between days 7 to 14 after the surgery. Results: Six subjects had dizziness complaints after CI: instability ( N  = 2), imbalance ( N  = 2) and vertigo ( N  = 2). The postoperative vHIT test turned abnormal only in subjects with vertigo as compared to the preoperative vHIT test results. Conclusion and significance: vHIT is a good vestibular function test during the first 2 weeks after CI surgery when vertigo is the main complaint